Effect of antacid gastric syrups on surface properties of dental restorative materials: an in vitro analysis of roughness and microhardness - Fikri Öcal; Burak Dayi (BMC Oral Health)
Summary Objectives The aim of this in-vitro study was to evaluate the effects of antacid gastric syrups on the surface roughness and microhardness of restorative dental materials. Materials and methods Three different composite resins, nanohybrid, microhybrid and giomer, and four antacid gastric syrups were used in the study. A total of 150 samples were obtained by preparing 50 (10 mm x 2 mm) disk-shaped samples of each composite type. The composites were randomly divided into 5 subgroups and immersed in antacid syrups for 2 min every day for 28 days. The control group samples were kept in distilled water for 28 days. Surface roughness was measured at the beginning, on the 7th, 15th and 28th days using a mechanical profilometer, AFM, and SEM and microhardness was measured using a Vickers device. Shapiro-Wilk, Repeated Measures ANOVA, One-Way ANOVA, Tukey and Games-Howell tests were applied for statistical analysis. Results After 28 days, the surface roughness of the giomer composite decreased significantly (p < 0.05). The surface roughness of microhybrid and nanohybrid composites increased slightly but not significantly (p > 0.05). Microhardness values of microhybrid and giomer composites showed a significant decrease (p < 0.05). SEM and AFM results were in agreement with the mechanical profilometer findings. Conclusion Agents such as calcium carbonate, sodium bicarbonate and magnesium carbonate in antacid gastric syrups can affect the surface properties of restorative dental materials. This may adversely affect the longevity and aesthetics of restorations. Clinical significance The study emphasizes the need for caution in restorative material selection and care protocols in patients using antacid gastric syrups.